Visual function restoration in a mouse model of Leber congenital amaurosis via therapeutic base editing - Dong Hyun Jo; Hyeon-Ki Jang; Chang Sik Cho; Jun Hee Han; Gahee Ryu; Youngri Jung; Sangsu Bae; Jeong Hun Kim (Molecular Therapy: Nucleic Acids, 2023)
Leber congenital amaurosis (LCA), an inherited retinal degeneration, causes severe visual dysfunction in children and adolescents. In patients with LCA, pathogenic variants, such as RPE65, are evident in specific genes, related to the functions of retinal pigment epithelium and photoreceptors. In contrast to the original Cas9, base editing tools can correct pathogenic substitutions without generation of DNA double-stranded breaks (DSBs). In this study, dual adeno-associated virus (AAV) vectors containing split adenine base editors (ABEs) with trans-splicing intein were prepared for in vivo base editing in retinal degeneration of 12 (rd12) mice, an animal model of LCA, possessing a nonsense mutation of C to T transition in the Rpe65 gene (p.R44X). Subretinal injection of AAV-ABE in retinal pigment epithelial cells of rd12 mice resulted in an A to G transition. The on-target editing was sufficient for recovery of wild-type mRNA, RPE65 protein, and light-induced electrical responses from the retina. Compared with our previous therapeutic editing strategies using Cas9 and prime editing, or with the gene transfer strategy shown in the current study, our results suggest that, considering the editing efficacy and functional recovery, ABEs could be a strong, reliable method for correction of pathogenic variants in the treatment of LCA.